Investigação dos inversores de ponto neutro grampeado em sistemas fotovoltaicos conectados à rede elétrica - Reis, Joaquim Henrique (2019)
This work presents a photovoltaic energy system connected to the grid. More specifically, the renewable energy and injected current conditioning. Initially, it is presented a brief description about photovoltaic structures, as solar resource, cell's technologies, I-V curves and MPPT algorithms. Then, it follows a state-of-art review about most common topologies and modulation techniques, in which it is stressed the choice of NPC-3L associated with an inductive filter. The control of grid connected systems includes outer voltage loop, Phase Locked Loop, in order to synchronization, inner current loop and protection schemes design. In this case, the under and overvoltage at DC bus , AC overload and anti-islanding strategies are mentioned. About the prototype, it is showed physical components and their limitations, as well as the methods applied, which they became feasible the experimental analysis: DSP, sensors and gate drivers. At last, the results present some internal open-loop signals, as static gain curve, voltage and current waveforms in semiconductors and PLL dynamics. About grid connected systems, it compares the terminal compensation previously to the modulation. In other words, it refers to AC and DC voltage signals that it evaluates control action signal at output current loop. In this case, if the DC voltage is the reference or the instantaneous value, with AC component, the dynamics is not the same. Moreover, there are differences if the AC voltage is the PLL output, without harmonics, or a grid measurement. So, the efficiency, power quality, and steady state waveforms highlight about the potential aspects and limitations of this research.